A Method for Assessing the Potential of Multifunctional Retrofitting of Rural Roofs Based on GF-2 Remote Sensing Imagery - Junqi Wang; Linlin Cheng; Yang Zheng; Huizhen Cui; Mengyao Zhu (Sensors)
Green roofs and photovoltaic (PV) roofs are important forms of roof retrofitting, and unused rural roofs provide favorable conditions for the development of green roofs and PV roofs. Here, this study proposes a new method for assessing the potential of multifunctional retrofitting of rural roofs. Firstly, rural roof types were classified into three categories based on GF-2 imagery: flat roofs, east–west pitched roofs, and north–south pitched roofs. The roof types were extracted based on the revised U-Net model, which aims to enhance the extracted features of the buildings and improve the perception of the buildings. Secondly, three types of retrofits—PV roofs, green roofs, and PV-green roofs—were designed taking into account the type, orientation, and area of the roofs. Finally, the potential electricity and carbon benefits of the different retrofit types of roofs were calculated separately, with the aim of realizing an assessment of the potential for roof retrofitting in the rural areas of Mentougou, Beijing. The results of the study showed that 35,407 (281.97 ha) roofs could be used for multifunctional retrofitting. If rural roofs are retrofitted with multifunctionality according to the methodology of this paper, they can absorb an additional 4.66 × 104 kg/yr of CO2 and increase biomass production by 0.99 × 104 kg/yr compared to retrofitting only PV roofs, and they can generate an additional 34.1 GWh/yr of electricity and reduce CO2 emissions by an additional 3.3 × 107 kg/yr compared to retrofitting to both PV roofs and green roofs. The assessment methodology of this study provides decision makers with data references on the multifunctional potential of rural rooftops for retrofitting, which can optimize the use of rural rooftops, and at the same time is important for promoting the energy transition in rural areas.